ABOUT THE EVALUATION OF THE LONGITUDINAL FORCES LEVEL EFFECTING THE TRACK DISPLACEMENT AT TRANSIENT MODES OF TRAIN MOVEMENT - Horobets, V. L.; Masleieva, L. H.; Ursuliak, L. V.; Arsonov, V. V. (Science and Transport Progress, 2015)
Purpose. Study the transient modes effect of movement on the track displacement for the freight train safety control is supposed in this paper. For this it is necessary to investigate the longitudinal dynamics of a train on the track displacement. Simultaneously to assess the longitudinal forces level of a track and rolling stock interaction. Methodology. The level of the longitudinal forces, effecting the track displacement, was evaluated using mathematical modeling of longitudinal vibrations of the trains at transient modes of motion caused by braking. It was considered that each train vehicle consists of a body (solid) and the wheel sets, connected with the body by friction bearings (inelastic link). It was believed that during the movement of each train vehicle the vertical plane of its symmetry coincident with the vertical plane of symmetry of the assembled rails and sleepers. At simulation it was also supposed that in the process of translational motion of the vehicle body wheels make pure rolling along the rail without slipping on it. Findings. In the results of calculations the values of the longitudinal forces at different types of braking were obtained (it is regenerative braking and pneumatic one) under quasi-static and shock transients. For this various initial state of clearances in the inter-car connections up to beginning of transient was considered. The level of dynamic additives to longitudinal forces of interaction between wheel and rail that are substantially depending on vehicle accelerations was assessed. Originality. The transient regimes effect of trains movement caused by braking on the level of the longitudinal forces of track and rolling stock interaction was investigated. The longitudinal load of freight trains with regenerative and pneumatic braking was researched. The effect of the initial state of the train and different modes of braking on a dynamic additive to the longitudinal forces of the interaction between the track and rolling stock, which may effect the displacement of assembled rails and sleepers, was estimated. Practical value. The obtained results can be used to select rational modes of braking of freight trains, especially on lengthy down grade, from the positions prevent possible track displacement.